Identification of telomere-related genes in the progression of colon adenocarcinoma: a bioinformatics analysis - Wang, Zhiyong; Zhang, Shuomin; Dong, Yi; Li, Zhikai; Li, Zizhan; Luan, Zhigang; Wang, Sen; Liu, Jipan; Li, Yong (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Telomeres play a crucial role in chromosomal stability and cancer development. However, the prognostic significance of telomere-related genes (TRGs) in colon adenocarcinoma (COAD) remains unexplored.Methods: RNA sequencing (RNA‑Seq) data of COAD with corresponding patient survival data from The Cancer Genome Atlas (TCGA), and TRGs from TelNet were used. A prognostic model was created by univariate/multivariate Cox regression analyses. Meanwhile, a nomogram was created for overall survival (OS) prediction. In addition, immune microenvironment [Cell‑type Identification By Estimating Relative Subsets Of RNA Transcripts (CIBERSORT), Tumor Immune Dysfunction and Exclusion (TIDE), single‑sample Gene Set Enrichment Analysis (ssGSEA), and immune checkpoint gene analysis] and drug sensitivity [half‑maximal inhibitory concentration (IC50)] analyses were performed.Results: This identified six key TRGs (USP2, TRIM7, EPHA6, IP6K3, CALML6, and COCH) significantly associated with patient outcome. A nomogram incorporating these genes demonstrated robust predictive ability for OS, with areas under the curve (AUCs) of 0.746, 0.750, and 0.726 for 1-, 2-, and 3-year OS, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses revealed that these genes were involved in cancer‑related pathways. Furthermore, distinct immune infiltration patterns, characterized by significant negative correlations between risk scores and activated CD8+ T cells as well as Memory B cells, were observed between high- and low-risk patient groups. Dasatinib, docetaxel, erlotinib, and gefitinib were identified as potential therapeutic candidates for high-risk patients. Finally, the differential expression of EPHA6 between COAD and normal tissues was validated by immunohistochemical (IHC) staining and Western blotting.Conclusions: Our findings establish TRGs as critical genetic determinants and powerful predictors of COAD prognosis, offering insights into potential therapeutic targets.